THE SCHOOL CLUSTER WORKING GROUP AS A MEDIA TO IMPROVE THE PERFORMANCE OF ELEMENTARY SCHOOL TEACHERS (Case Study of the Working Group Teachers Cluster II Tinggimoncong District) - Pitri Ana; Rosleny Babo Babo; Muhammad Nawir (JURNAL PAJAR (Pendidikan dan Pengajaran), 2020)
This study aimed 1) to find out the management system of the Teachers’ Team Work from Bawakaraeng Cluster in Tinggimoncong district, 2) to analyze the steps taken by the Teachers’ Team Work, and 3) how effective it is in improving teacher performance in Tinggimoncong district .This research was a qualitative research by using a case study approach. The study was conducted in Cluster II, Tinggimoncong District, Gowa Regency. The samples in this study were 15 people. The data were collected through direct observation, interviews and documentation. The results showed that the Bawakaraeng Teachers’ Team Work had not yet managed the organization maximally. The visible step taken by the KKG group in Tinggimoncong district was the change in the KKG system from the Cluster KKG to the class KKG and the work program compiled in the class KKG was chosen based on the results of discussions from each group of class teachers, and was chosen based on priority scale. The effectiveness of Bawakaraeng KKG is influenced by supporting and inhibiting factors. Supporting factors include: changes in the KKG pattern, interesting material, continuing KKG implementation, motivation from superiors. Inhibiting factors include: lack of government attention to the Teachers’ Team Work and lack of funding.